2022
DOI: 10.1167/iovs.63.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescent Organelles Within the Retinal Pigment Epithelium in Human Donor Eyes With and Without Age-Related Macular Degeneration

Abstract: Purpose Human retinal pigment epithelium (RPE) cells contain lipofuscin, melanolipofuscin, and melanosome organelles that impact clinical autofluorescence (AF) imaging. Here, we quantified the effect of age-related macular degeneration (AMD) on granule count and histologic AF of RPE cell bodies. Methods Seven AMD-affected human RPE-Bruch's membrane flatmounts (early and intermediate = 3, late dry = 1, and neovascular = 3) were imaged at fovea, perifovea, and near periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…A recent histologic study showed that in AMD RPE cells, intracellular organelle distribution (apical: melanosomes/melanolipofuscin; basal/basolateral: lipofuscin dominated) was comparable to aged RPE cells. 42 Further, this study showed that lipofuscin and melanolipofuscin, the predominant source of short-wavelength AF of the human RPE, were reduced in AMD RPE cells. 42 Histologic studies have documented RPE degranulation, shedding, and anterior migration to be at least partly culpable for the reduced AF of the monolayer.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A recent histologic study showed that in AMD RPE cells, intracellular organelle distribution (apical: melanosomes/melanolipofuscin; basal/basolateral: lipofuscin dominated) was comparable to aged RPE cells. 42 Further, this study showed that lipofuscin and melanolipofuscin, the predominant source of short-wavelength AF of the human RPE, were reduced in AMD RPE cells. 42 Histologic studies have documented RPE degranulation, shedding, and anterior migration to be at least partly culpable for the reduced AF of the monolayer.…”
Section: Discussionmentioning
confidence: 64%
“… 42 Further, this study showed that lipofuscin and melanolipofuscin, the predominant source of short-wavelength AF of the human RPE, were reduced in AMD RPE cells. 42 Histologic studies have documented RPE degranulation, shedding, and anterior migration to be at least partly culpable for the reduced AF of the monolayer. 1 Further, there is an increasing amount of evidence that AMD is associated with decreased rather than increased autofluorescence in clinical imaging.…”
Section: Discussionmentioning
confidence: 64%
“…On a cellular and subcellular level, FAF mainly originates from fluorophores in the outer retina and the retinal pigment epithelium (RPE). In RPE cells, these fluorophores are linked to intracellular granules, which show different autofluorescence (AF) properties: melanolipofuscin and lipofuscin granules with peak excitation in the short wavelength and melanin in melanosomes and melanolipofuscin granules with peak excitation in the near-infrared (IR) spectrum 3–5…”
Section: Introductionmentioning
confidence: 99%
“…Lipofuscin and melanolipofuscin arise as a byproduct of this phagocytosis and are accumulated from a family of autofluorescent bisretinoid compounds at the level of the RPE that can be measured using AF imaging devices. [15][16][17] Autofluorescence in patients with CSC shows multiple patterns, including mottled, hypofluorescent, and hyperfluorescent patterns. 18 In the acute phase, CSC shows a decreased AF signal, presumably caused by the presence of subretinal fluid underneath the retinal detachment.…”
mentioning
confidence: 99%
“…Lipofuscin and melanolipofuscin arise as a byproduct of this phagocytosis and are accumulated from a family of autofluorescent bisretinoid compounds at the level of the RPE that can be measured using AF imaging devices. 15–17…”
mentioning
confidence: 99%